Cytochrome P450 as Dimerization Catalyst in Diketopiperazine Alkaloid Biosynthesis. Issue 5 (13th February 2014) - Saruwatari, Takayoshi; Yagishita, Fumitoshi; Mino, Takashi; Noguchi, Hiroshi; Hotta, Kinya; Watanabe, Kenji
Abstract As dimeric natural products frequently exhibit useful biological activities, identifying and understanding their mechanisms of dimerization is of great interest. One such compound is (−)‐ditryptophenaline, isolated from Aspergillus flavus, which inhibits substance P receptor for potential analgesic and anti‐inflammatory activity. Through targeted gene knockout in A. flavus and heterologous yeast gene expression, we determined for the first time the gene cluster and pathway for the biosynthesis of a dimeric diketopiperazine alkaloid. We also determined that a single cytochrome P450, DtpC, is responsible not only for pyrroloindole ring formation but also for concurrent dimerization of N‐methylphenylalanyltryptophanyl diketopiperazine monomers into a homodimeric product. Furthermore, DtpC exhibits relaxed substrate specificity, allowing the formation of two new dimeric compounds from a non‐native monomeric precursor, brevianamide F. A radical‐mediated mechanism of dimerization is proposed.